2019
DOI: 10.3934/publichealth.2019.4.514
|View full text |Cite
|
Sign up to set email alerts
|

Iranian physicians’ expectations of telemedicine development and implementation infrastructures in teaching hospitals

Abstract: IntroductionIn spite of the fact that telemedicine has various advantages; similarly as in some other data systems, it is essential to investigate clients' perspective of technology. Besides, the clients' awareness and satisfaction of the telemedicine are significant issues that ought to be considered before starting a telemedicine program. The present examination in this way looks to assess Iranian doctors' demeanor and recognition toward the infrastructures of telemedicine development and implementation.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…[ 21 28 ] Likewise, in other studies, most of the doctors interviewed had a favorable attitude toward the real-life utilization of telemedicine. [ 16 29 30 ] But the study conducted by Ashfaq et al . 2020[ 31 ] concluded differently as 28.1% of the participants opined that telemedicine might help provide medical care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 21 28 ] Likewise, in other studies, most of the doctors interviewed had a favorable attitude toward the real-life utilization of telemedicine. [ 16 29 30 ] But the study conducted by Ashfaq et al . 2020[ 31 ] concluded differently as 28.1% of the participants opined that telemedicine might help provide medical care.…”
Section: Discussionmentioning
confidence: 99%
“…The studies conducted by Sheikhtaheri et al .,[ 29 ] 2016, Ghafari et al . 2019,[ 30 ] and Ullah et al . 2020[ 36 ] reported that 43.7, 35.5, and 46% of the participants, respectively, were aware of telemedicine.…”
Section: Discussionmentioning
confidence: 99%
“…Telehealth services in Iran have several challenges. The foremost include the absence of any definite strategy, vague and complex IT organization, cultural and awareness issues, funding e-health system and weak implementation (Ghafari et al, 2019). Another common obstacle towards implementing telehealth is the lack of motivation and ethos in the public.…”
Section: Challenges Of Telemedicine Adoptionmentioning
confidence: 99%